Recent advances of plasmonic elemental Bi based photocatalysts in environmental remediation and energy conversion. (15th March 2023) - Yue, Cailiang; Zhu, Linlin; Qiu, Yixing; Du, Zhiling; Qiu, Jinli; Liu, Fuqiang; Wang, Fenghe
Abstract: Photocatalysis is a quite promising technique to solve increasingly energy shortage and environmental pollution. Due to the specific electronic and optical properties, recent years have seen a booming development of elemental bismuth-based plasmonic photocatalysts. In this review, the unique electronic and optical properties of elemental Bi are briefly summarized. Afterwards, a plenty of synthetic methods of elemental Bi nanomaterials with controllable size and morphology are systematically reviewed and compared, including wet-chemical reduction, solvothermal, electrochemical reduction, liquid-phase exfoliation and pyrolysis method. Subsequently, mechanistic understanding over elemental Bi-based plasmonic photocatalysts are also discussed. Besides, the photocatalytic applications in environmental remediation and energy conversion of elemental Bi-based plasmonic photocatalysts are arranged as well. In the end, we offer the personal expectations on the prospective development of this flourishing research area. This review is aimed to supply a helpful support on the rational design of efficient elemental Bi-based photocatalysts for energy conversion and environmental remediation. Graphical abstract: Image 1